Seroprevalence of some viral and bacterial zoonoses in domestic ruminants in Medina - Shabana, Iman Ibrahim; Krimly, Roaa A (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The study aimed to explore the seroprevalence of some bacterial (Brucella spp., Chlamydia abortus) and viral [Rift Valley fever virus (RVFV), foot and mouth disease virus (FMDV)] zoonoses in domestic ruminants in Medina. Materials and Methods: A total of 1,000 blood samples from 665 sheep, 228 goats, and 107 camels were collected from the central slaughterhouse, private farms, and veterinary clinics affiliated to the Ministry of Agriculture. The samples were screened using the Enzyme-Linked Immunosorbent Assay (ELISA). The results were statistically analyzed using Statistical Package for the Social Sciences version 20. Results: Brucella was found in 7.7%, 8.8%, and 6.5% of sheep, goats, and camel’s sera, respectively. In humans, Brucella abortus and Brucella melitensis had higher frequencies in males (61.3%, 59.8%) than in females (38.7%, 40.2%). Chlamydia abortus was reported only in sheep at a rate of 0.75%. RVFV was prevalent in sheep (10.7%) and goats (17.9%). FMDV was reported in 27.8% of sheep and 7.9% of goats. There was a highly statistical significance between Brucella, RVFV, and FMDV seropositivity and locally bred animals (p < 0.01). Multiple seropositivities have been reported among sheep and goats. Brucella was commonly observed in mixed infection with other bacterial and viral agents under study. Conclusion: The surveyed viral and bacterial agents were prevalent in ruminants in the Medina region. Since Medina is an important destination for pilgrims from all over the world, therefore, an integrated approach involving strict control measures and routine vaccination programs should be adopted to reduce the possibility of global epidemics. J. Adv. Vet. Anim. Res., 7(1): 42-50, March 2020